The Zn(II)2Cys6 transcription factor BcDIC affects the asexual reproduction of Botrytis cinerea by regulating pectinesterase genes - Shasha Lu; Xiaokang Zhang; Chang He; Guangjin Li; Tong Chen; Boqiang Li; Shiping Tian; Zhanquan Zhang (Phytopathology Research, 2023)
Abstract Botrytis cinerea is one of the most destructive plant pathogens, causing great economic losses in a wide variety of crops. It is difficult to control the pathogen because of its flexible mode of infection, high reproduction, genetic plasticity and strong stress resistance. There are more than 400 genes encoding transcription factors in the genome of B. cinerea, among which Zn(II)2Cys6(C6) transcription factors constitute the largest family. However, the mechanisms of Zn(II)2Cys6(C6) transcription factors regulating the development and pathogenicity of B. cinerea are largely unknown. In this study, we identified an important C6 transcription factor BcDIC that regulates the asexual reproduction and pathogenicity of B. cinerea. The virulence of the knockout mutant ΔBcDIC was reduced on various hosts. Especially, ΔBcDIC completely lost the ability of conidiation. By analyzing the transcriptome data, we found that deletion of ΔBcDIC enhanced the expression of pectinesterase family genes in B. cinerea. Furthermore, the results of yeast-one-hybrid and dual-LUC reporter assay suggested that BcDIC could bind to the promoter of two pectinesterase genes and suppress their expression. In this work, we identified a C6 transcription factor involved in the pathogenesis and asexual reproduction of B. cinerea, and the results implied that the capacity of pectin degradation was closely related with the reproduction process.